2018
DOI: 10.1158/1535-7163.mct-16-0847
|View full text |Cite
|
Sign up to set email alerts
|

ICEC0942, an Orally Bioavailable Selective Inhibitor of CDK7 for Cancer Treatment

Abstract: Recent reports indicate that some cancer types are especially sensitive to transcription inhibition, suggesting that targeting the transcriptional machinery provides new approaches to cancer treatment. Cyclin-dependent kinase (CDK)7 is necessary for transcription, and acts by phosphorylating the C-terminal domain (CTD) of RNA polymerase II (PolII) to enable transcription initiation. CDK7 additionally regulates the activities of a number of transcription factors, including estrogen receptor (ER)-α. Here we desc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
122
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(131 citation statements)
references
References 48 publications
5
122
0
Order By: Relevance
“…As a whole CDK7 inactivation dismantles two mechanisms needed for medulloblastoma proliferation and survival. These data are particularly relevant given the recent development of clinical grade CDK7 inhibitors (Hu et al, 2019a;Hu et al, 2019b;Patel et al, 2018). CDK7 inhibition with SY-5609 has already entered clinical trials (NCT04247126).…”
Section: Discussionmentioning
confidence: 99%
“…As a whole CDK7 inactivation dismantles two mechanisms needed for medulloblastoma proliferation and survival. These data are particularly relevant given the recent development of clinical grade CDK7 inhibitors (Hu et al, 2019a;Hu et al, 2019b;Patel et al, 2018). CDK7 inhibition with SY-5609 has already entered clinical trials (NCT04247126).…”
Section: Discussionmentioning
confidence: 99%
“…ICEC0942 is an orally bioavailable CDK7 inhibitor also being evaluated in preclinical studies (155). Whereas, THZ1 has a covalent mechanism of action and may interact with other kinases, ICE0942 has a non-covalent mechanism of action, which could possibly limit side effects (154,155). Oral administration of ICE0942 in mice showed favorable safety with no adverse effects on liver or kidney function (155).…”
Section: Cdk7 and Cdk9mentioning
confidence: 99%
“…S1). THZ1 inhibits CDK7 by covalently targeting a cysteine residue (C312), which lies outside the ATP-binding domain [10], whereas ICEC0942 is an ATP-competitive CDK7i [16]. It has been shown that mutation of C312 to serine (C312S), is sufficient to prevent THZ1 from covalently binding to CDK7 and from inhibiting CDK7 activity [10], therefore it was possible that a mutation of C312 could be responsible for the THZ1-resistance and continued sensitivity to ICEC0942 in MCF7-THZ1 R .…”
Section: Creation Of Breast Cancer Cell Lines With Resistance To Thz1mentioning
confidence: 99%
“…Whole cell lysates were prepared in RIPA buffer (Sigma-Aldrich), supplemented with protease and phosphatase inhibitors (Roche, UK), and immunoblotting was carried out as previously described [16]. Antibodies used were; Pol II (ab26721), Pol II-phosphoserine-2 (ab5095), Pol IIphosphoserine-5 (ab5131), Pol II-phosphoserine-7 (ab126537) and β actin (ab6276), purchased from Abcam (Cambridge, UK), and ABCB1 (D3H1Q) and ABCG2 (4477), purchased from Cell Signaling Technology (Danvers, MA, USA).…”
Section: Immunoblottingmentioning
confidence: 99%
See 1 more Smart Citation